2022
DOI: 10.3390/biomedicines10061341
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nomograms for Predicting Prognosis of Pancreatic Cancer after Pancreatectomy: A Multicenter Study

Abstract: Surgical resection is the only curative treatment for pancreatic ductal adenocarcinoma (PDAC). Currently, the TNM classification system is considered the standard for predicting prognosis after surgery. However, the prognostic accuracy of the system remains limited. This study aimed to develop new predictive nomograms for resected PDAC. The clinicopathological data of patients who underwent surgery for PDAC between 2006 and 2015 at five major institutions were retrospectively reviewed; 885 patients were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Nomograms, as a reliable and convenient tool for individual risk prediction, have been widely used in the medical field and for guiding clinical decision ( 37 , 38 ). The C-index and AUC are the main reference for evaluating the predictive performance of a nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms, as a reliable and convenient tool for individual risk prediction, have been widely used in the medical field and for guiding clinical decision ( 37 , 38 ). The C-index and AUC are the main reference for evaluating the predictive performance of a nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…These factors, including LODDS, age at diagnosis, sex, tumor size, and radiation status, were included in the final models. Based on the multivariate Cox proportional hazards regression model, a novel nomogram was generated to predict the CSS in patients with SCLC using the “rms” package [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we investigated the predictive value of 12 clinicopathologic variables (gender, age, tumor size, degree of differentiation, tumor location, TNM stage, lymph node metastasis, vascular cancer thrombus, peripheral nerve invasion, CEA, CA199, CA125) for resectable pancreatic ductal adenocarcinoma, and many attempts have been made to determine the prognostic factors of PDAC in addition to several well-known factors such as TNM stage and carbohydrate antigen 19 − 9 (CA19-9) [25],In several previous studies, LN status and degree of tumor differentiation were identified as prognostic factors for resectable PDAC [26][27][28],and these findings are consistent with the results of this study, which suggest that LN status and degree of differentiation are independent prognostic factors in patients with PDAC. In addition, studies have shown that neoadjuvant chemotherapy can inhibit tumor progression and effectively prolong postoperative survival [29].however, there is still a lack of uniform criteria for selecting patients who are candidates for neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%